1991
DOI: 10.1177/0148607191015006619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive Performance of Nutritional Indicators by Receiver‐Operating Characteristic Curve Analysis

Abstract: Four hundred twenty-two cancer patients who underwent major surgery were studied. At admission, nutritional status was evaluated in all patients by assessing serum albumin (SA), total iron-binding capacity (TIBC), total lymphocyte count (TLC), serum cholinesterase activity (CHE), and weight loss (WL). All patients received perioperative short-term antibiotic prophylaxis and postoperative total parenteral nutrition. Prognostic ability of nutritional indicators was assessed by receiver-operating characteristic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…12,13 Biohumoral prognostic factors, on the other hand, have been investigated to a lesser degree, even though some have confirmed predictive value. [14][15][16][17][18][19][20][21][22][23] Prognostic scores have been described for postsurgical, 24,25 advanced, 26 and geriatric 27 cancer patients; moreover, "intensity" and "acuity" scores have been elaborated for different stages of the disease. 28,29 Our group planned 30 a prospective multicenter study on more than 500 terminally ill cancer patients (training set) to identify clinical 13 and biological 23 prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Biohumoral prognostic factors, on the other hand, have been investigated to a lesser degree, even though some have confirmed predictive value. [14][15][16][17][18][19][20][21][22][23] Prognostic scores have been described for postsurgical, 24,25 advanced, 26 and geriatric 27 cancer patients; moreover, "intensity" and "acuity" scores have been elaborated for different stages of the disease. 28,29 Our group planned 30 a prospective multicenter study on more than 500 terminally ill cancer patients (training set) to identify clinical 13 and biological 23 prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were further confirmed by comparing CD3zeta levels in the serum of breast cancer patients and healthy controls by ELISA and ROC curve analysis. Analysis of ROC curves provides a useful parameter for evaluating the clinical usefulness of a respective biomarker, and an AUC of 0.5 signifies that detection of a respective biomarker would correctly identify disease or health states 50% of the time (Braga et al, 1991;Fluss et al, 2005;Perkins et al, 2005;Schisterman et al, 2005;Akobeng, 2007;Hao et al, 2008). The AUC of CD3zeta was 0.837, meaning that identification of CD3zeta can be used CD3zeta is a breast cancer biomarker as an adjuvant serum biomarker for breast cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple logistic analysis and the receiver operating characteristics (ROC) curve analysis were used to address these issues. This approach was chosen because previous experiences showed that ROC analysis was a reliable statistical method to identify threshold values of other indices related to postoperative infections [11,12].…”
Section: Introductionmentioning
confidence: 99%